Emerging market analysis of passive and active investing under bear and bull market conditions - Thabo J. Gopane; Noel T. Moyo; Lesego F. Setaka (Journal of Capital Markets Studies (JCMS), 2024)
Purpose Stirred by scant regard for market phases in portfolio performance assessments, the current paper investigates the active versus passive investment strategies under the bull and bear market conditions in emerging markets focusing on South Africa as a case study. Design/methodology/approach Methodologically, the measures of Jensen's alpha and Treynor index are applied to the monthly returns of 20 funds from January 2010 to June 2022. Findings The results are enlightening; though they contradict developed market evidence, they are consistent with emerging market trends. The findings show that actively managed funds outperform the market benchmark and passive investing style under bear and normal market conditions. Passive investment strategy outperforms both market benchmark and actively investing style under bull market conditions. Practical implications In the face of improved market efficiency, increased liquidity and recent technological impact, the findings of this study have practical application. The study outcomes should inform and update global investors, especially asset managers interested in emerging markets; however, the limitations of the study should also be considered. Originality/value While limited studies consider market conditions when comparing and contrasting the performance of passive versus active investing, such consideration is lacking in emerging markets. The current study corrects this literature imbalance.
Keywords: G10; G11; G12; 330; Active investing; Bear; Bull; Emerging market; Passive investing; Performance measure; Unit trust